Effect of Reminiscence Therapy on Reducing Depression in the Elderly - Pratiwi Gasril; Uswatul Khasanah; Dewi Anggraini; Yeni Devita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The prevalence of depression in the elderly population is estimated to be 1-2%, female prevalence 1.4%, and male prevalence 0.4%. Depression in the elderly is very common and significantly reduces the quality of life of the elderly. This study aims to determine effect of reminiscence therapy on reducing depression in the elderly. This type of research is a quantitative study with a quasy experiment with control group design. The population in this study were all elderly people who were in Rukun Warga 08, Delima Village, Binawidya District, Work Area of Sidomulyo Community Health Center Inpatient Pekanbaru City. The sample of the study was elderly people who experienced depression as many as 22 people who were divided into 2 groups, namely the control group and the intervention group with 11 people in each group. Determination of the sample is based on the inclusion and exclusion criteria. Inclusion criteria were elderly aged 60 years with mild to moderate depression (geriatric depression score), good and cooperative awareness, and not taking antidepressant drugs. Analysis of the data using the wilcoxon test statistical test. The results of the study in statistical tests showed that there were differences in depression scores in the elderly before and after reminiscence therapy, so it can be concluded that there is an effect of reminiscence therapy on reducing depression in the elderly. There needs to be a commitment from nursing staff in implementing reminiscence therapy as a nursing intervention to prevent and reduce depression in the elderly.